2010
DOI: 10.1007/s11926-010-0108-z
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic Arthritis: Pharmacotherapy Update

Abstract: Psoriatic arthritis is a systemic disorder that causes chronic pain, altered physical appearance, and loss of function. The clinical features are diverse, but the core manifestations are psoriasis, peripheral arthritis, axial disease, enthesitis, and dactylitis. Our understanding about the psoriatic arthritis disease state, assessment, and treatment has advanced thanks to significant collaborative efforts by rheumatologists and dermatologists in the development of classification criteria, outcome measures to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 44 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…It has been validated in assessment of psoriasis and shows discrimination and responsiveness in PsA trials [5759]. …”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…It has been validated in assessment of psoriasis and shows discrimination and responsiveness in PsA trials [5759]. …”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…Studies have shown that IL‐17 is involved in innate and adaptive immunity, and triggers and initiates inflammation . In recent years, many studies have found that IL‐17 is closely related with AS pathogenesis and many AS drugs for reducing IL‐17 have been developed …”
Section: Introductionmentioning
confidence: 99%
“…[5] In recent years, many studies have found that IL-17 is closely related with AS pathogenesis and many AS drugs for reducing have been developed. [6][7][8] Bilobalide (BIL) is a sesquiterpene compound extracted from the dried leaves of Ginkgo biloba. G biloba extract-761 (EEGb-761) is a combination of G biloba and other G biloba extracts.…”
Section: Introductionmentioning
confidence: 99%
“…6 Small molecule inhibitors of RORc have also demonstrated efficacy in animal models. [7][8][9][10][11][12][13][14] Examples of recently reported RORc inverse agonists include TMP778 (1), GSK805 (2) and compound 3. 15, 16 We herein report the discovery of a series of novel pyrazole-containing benzamides as potent RORc inverse agonists (Fig.…”
Section: Introductionmentioning
confidence: 99%